Family in China: later marriage, spousal bargaining and intra-household decision making - Bao, Kun (2020)
The family is the basic socio-economic unit for society, as it is regarded as crucial to organise income generation, allocate resources to its members and provide emotional and welfare support among many other activities. Despite major changes over time and enormous variations across social and economic environments, the family remains the most influential of all institutions. Through the analysis of the family, one could not only gain a thorough understanding of the social change but also give a scientific prediction of an individual’s economic behaviour. Therefore, whether in the field of Economics or Sociology, the study of the family is getting more and more attention.